A correlation between students’ habit in watching english movie playing online mobile game, and vocabulary achievement of the eleventh grade of vocational high school 1 galang tolitoli - Jaya, Jaya; Hidayati, Hidayati; Syahrial, Syahrial (Universitas Madako Tolitoli, 2024)
This study aims to find out whether there is a significant relationship between students' English movie viewing habits and their vocabulary improvement. The purpose is to determine whether there is a significant relationship between online mobile game play and vocabulary success. To find out whether there is a significant relationship between students' English movie watching, online gaming habits, and vocabulary improvement. This study is a quantitative research design. The sample consisted of ten 11th-grade students from a specially selected Vocational High School 1. Data was collected through questionnaires and tests. The results of this study show that there is no significant relationship between students' English movie viewing habits and vocabulary acquisition. However, there is a very weak correlation based on the coefficient. Based on the coefficients, there is no significant correlation between online mobile game play and vocabulary success, although the correlation is very weak. There is no significant relationship between students' English movie watching, online mobile gaming habits, and vocabulary achievement, but there is a weak correlation based on the coefficient.